Sistem Pengelolaan Zakat Di Era Modern - Tafsiruddin Tafsiruddin (LPPM STAI Diniyah Pekanbaru, 2020)
Zakat is one of the pillars of Islam that is required for every people Muslim who is able, either male or female. Position zakat is very important in Islam case is indeed order by Allah SWT, and also many hadiths prophet explained about the obligation to zakat on property objects were in had. Need we understand together that the charity is worship that not only has the value of the relationship vertical, between humans by Allah, but the charity also has the value of the lives of human beings will be harmony, the rich will gain the satisfaction of the mind because it could help fellow Muslims who may be less capable, and that less capable of (poor) to utilize the wealth of zakat are accepted from those capable of (wealthy) who have issued their zakat. With the charity hopes the needs of the ummah who are less able to be fulfilled, including among others the alleviation of poverty. Zakat will run with good, effective, and precise target when property zakat in governance with management was good as well, especially in the era Hp at the moment is actually also adds convenience for the Muzakki to pay zakat on property and himself. History has proved that the implementation of the program of zakat which has been implemented by the institutions of zakat or carried out by the companions of the Prophet was actually able to alleviate poverty, help the person who is weak, even at times reign of Caliph Umar bin Abdul Aziz until no there are entitled to receive zakat because the entire population is already wealthy or already be Muzakki (people who tithe)